The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00167-014-3316-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted navigation is beneficial both in primary and revision surgery with modular rotating-hinge knee arthroplasty

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a cadaver model, Wang et al could show that placing IS-Joint screws with the help of AR is possible with minimal deviation and without lesions to vessels or nerval structures [ 8 ]. Ochs and Gonser demonstrated that with the help of three-dimensional navigation, radiation exposure could be reduced [ 9 ]. A reduction in radiation dose is very important, since especially in these procedures, radiation doses experienced by the surgical team are high [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaver model, Wang et al could show that placing IS-Joint screws with the help of AR is possible with minimal deviation and without lesions to vessels or nerval structures [ 8 ]. Ochs and Gonser demonstrated that with the help of three-dimensional navigation, radiation exposure could be reduced [ 9 ]. A reduction in radiation dose is very important, since especially in these procedures, radiation doses experienced by the surgical team are high [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ochs et al presented the results of primary and revision TKA with EnduRo, which was implanted using a navigation system [ 19 ]. In this study, significantly better kKSS values and ROM were obtained in the Primary group than in the Revision group, whereas no differences were observed for fKSS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absorbable suture fixation was verified to be a simple and dependable fixation method, which is also affordable (50). Nowadays, the computer-assisted navigation and preoperative software have been introduced to improve the accuracy in revision surgery (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%